2014
DOI: 10.3389/fnhum.2014.00078
|View full text |Cite
|
Sign up to set email alerts
|

Associations between prefrontal cortex activation and H-reflex modulation during dual task gait

Abstract: Walking, although a largely automatic process, is controlled by the cortex and the spinal cord with corrective reflexes modulated through integration of neural signals from central and peripheral inputs at supraspinal level throughout the gait cycle. In this study we used an additional cognitive task to interfere with the automatic processing during walking in order to explore the neural mechanisms involved in healthy young adults. Participants were asked to walk on a treadmill at two speeds, both with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 46 publications
3
77
0
1
Order By: Relevance
“…all articles measured the behavioral and neural activity changes. (Gruber 2001;Matthews, Garry et al 2006;Just, Keller et al 2008;Matthews, Martin et al 2009;Serrien 2009;Gazes, Rakitin et al 2010;Remy, Wenderoth et al 2010;Holtzer, Mahoney et al 2011;Van Impe, Coxon et al 2011;Johnson and Shinohara 2012;Doi, Makizako et al 2013;Johannsen, Li et al 2013;Mandrick, Derosiere et al 2013;Ohsugi, Ohgi et al 2013;Wu, Liu et al 2013;Beurskens, Helmich et al 2014;Blumen, Holtzer et al 2014;De Sanctis, Butler et al 2014;Meester, Al-Yahya et al 2014;Mirelman, Maidan et al 2014;Nijboer, Borst et al 2014;Kwon, Lim et al 2015;Malcolm, Foxe et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…all articles measured the behavioral and neural activity changes. (Gruber 2001;Matthews, Garry et al 2006;Just, Keller et al 2008;Matthews, Martin et al 2009;Serrien 2009;Gazes, Rakitin et al 2010;Remy, Wenderoth et al 2010;Holtzer, Mahoney et al 2011;Van Impe, Coxon et al 2011;Johnson and Shinohara 2012;Doi, Makizako et al 2013;Johannsen, Li et al 2013;Mandrick, Derosiere et al 2013;Ohsugi, Ohgi et al 2013;Wu, Liu et al 2013;Beurskens, Helmich et al 2014;Blumen, Holtzer et al 2014;De Sanctis, Butler et al 2014;Meester, Al-Yahya et al 2014;Mirelman, Maidan et al 2014;Nijboer, Borst et al 2014;Kwon, Lim et al 2015;Malcolm, Foxe et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…However, they compared brain activity during a DT with the brain activity during the motor ST only, therefore we lack information about the activation during the cognitive ST (Holtzer, Mahoney et al 2011;Doi, Makizako et al 2013;Ohsugi, Ohgi et al 2013;Meester, Al-Yahya et al 2014;Mirelman, Maidan et al 2014). All studies involved lower limb movements in terms of walking or standing (Holtzer, Mahoney et al 2011;Doi, Makizako et al 2013;Ohsugi, Ohgi et al 2013;Meester, Al-Yahya et al 2014;Mirelman, Maidan et al 2014).…”
Section: D) Miscellaneous Of Under- Over-and Additive Activationsmentioning
confidence: 99%
“…In addition, the combination of exercise and brain training, the dual-task is considered to be more effective than doing the single task. Previous studies utilizing brain training have reported cortical activation during dual-task interference [23] and increased activation of the prefrontal cortex (PFC) [24,25]. In addition, dual-task had wider effective range compared to single-task.…”
Section: Discussionmentioning
confidence: 99%
“…This is evident from studies demonstrating increased cortical activity during the performance of walking tasks that require adaptability (Clark, Rose, Ring, & Porges, 2014; Koenraadt, Roelofsen, Duysens, & Keijsers, 2014; Meester, Al-Yahya, Dawes, Martin-Fagg, & Pinon, 2014). The complexity of the environment and the demands placed on the individual while walking on uneven terrain will likely result in heightened attentional demand and potential interference with control processes for any other simultaneous motor or cognitive task (Clark, 2015).…”
Section: Implications Of Gait Adaptations During Uneven Terrain Nementioning
confidence: 98%